FRONTABSCHNITT HOCHSCHULE. - GÖLLNITZ, MARTIN; PÖPPINGHEGE, RAINER (Westfälische Forschungen, 2023)
The article examines the processes of National Socialist power consolidation at the universities of Kiel and Münster (in Germany) on a student level between 1926 and 1936. It delves into the strategies, reactions, and perceptions of academic organizations during this period, detailing the rise of NS student groups and their challenges.